Activity and Stability of Immobilized Lipase for Utilization in Transesterification of Waste Cooking Oil - Azianna Gusniah; Harumi Veny; Fazlena Hamzah (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Biodiesel is fatty acid methyl ester that commonly derived from vegetable oils and animal fats that can be produced through enzymatic transesterification using lipase. In this study, three different types of lipase were used, which are Lipase Immobilized Pseudomonas cepacia, PcL, Thermomyces lanuginosus, TLIM, and Candida Antarctica A (recombinant from Aspergillus oryzae), CALA. These lipases were compared based on their activity at different pH (6-10), temperature (30-50 °C), activation energy, and amount of lipase loading for hydrolysis of p-NPA into n-NP. The result indicates that among the lipase used in the study, CALA is the preferable biocatalyst in the hydrolysis of p-NPA due to the minimum energy required and higher enzymatic activity at 20 mg of enzyme loading. PcL and CALA used in the study gave the optimum activity at pH 9 except for TLIM at pH 8 and the optimum temperature at 40 °C. The kinetic data obtained for CALA in this reaction were Km = 57.412 mM and Vm = 70 µM/min. This finding shows that CALA is beneficial biocatalysts for the transesterification process to obtain a higher product with lower activation energy. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).